Associations between Pain-Related Anxiety, Gender, and Prescription Opioid Misuse among Tobacco Smokers Living with HIV/AIDS. (10th November 2018) - LaRowe, Lisa R.; Chilcott, Lauren N.; Zvolensky, Michael J.; Vanable, Peter A.; Flood, Kelley; Ditre, Joseph W.
ABSTRACT: Background : People living with HIV/AIDS (PLWHA) who smoke cigarettes are vulnerable to greater pain and aberrant use of prescription pain medications. Prescription opioid misuse is highly prevalent among PLWHA and can lead to a variety of adverse outcomes. Pain-related anxiety, which has been implicated in the maintenance of both pain and tobacco dependence, may also play a role in prescription pain medication misuse. Objectives : This study aimed to test associations between pain-related anxiety and prescription opioid misuse. We hypothesized that, among those prescribed opioid medication, pain-related anxiety would be positively associated with current opioid misuse, and stated intentions to misuse prescription opioids in the future. We further hypothesized that these relations would be more pronounced among males (vs. females). Methods : Participants included 61 PLWHA daily tobacco smokers with pain. Hierarchical regressions were used to test interactions between gender and pain-related anxiety on current and intended opioid misuse among those prescribed opioid medications. Results : There was a significant interactive effect of pain-related anxiety and gender on opioid misuse, such that pain-related anxiety was positively associated with current opioid misuse among male (but not female) participants who were prescribed opioid medications. Among both males and females, pain-related anxiety was positively associated with intention to misuse prescription pain medications in the future. Conclusions/Importance : Additional research into the role of pain-related anxiety in prescription opioid misuse is warranted. This type of work may inform the development of tailored interventions for PLWHA smokers who are prescribed opioid pain medications.